2018
DOI: 10.1002/jso.24984
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic artery infusion of melphalan in patients with liver metastases from ocular melanoma

Abstract: HAI of melphalan is safe and feasible for patients with metastatic ocular melanoma. Further study to determine the optimal utilization of this treatment approach is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Siegel et al [ 58 ], also using fotemustine, reported an OS of up to 22 months, although it is not known how many of the patients included in the study received first-line therapy. On the other hand, the study by Boone et al [ 49 ], the most recent in this group, barely reached 3 months of OS with melphalan.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Siegel et al [ 58 ], also using fotemustine, reported an OS of up to 22 months, although it is not known how many of the patients included in the study received first-line therapy. On the other hand, the study by Boone et al [ 49 ], the most recent in this group, barely reached 3 months of OS with melphalan.…”
Section: Resultsmentioning
confidence: 65%
“…The median survival of the studies included in this review is around 15 months [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. The multi-center trial of Leyvraz et al [ 29 ] with fotemustine, one of the most powerful treatments in the review, is a perfect example of these results, with overall survival (OS) of 14 months and a PFI of 4.5.…”
Section: Resultsmentioning
confidence: 99%
“…For the palliative treatment of liver metastases in UM patients, HAIC is considered a valuable treatment option [ 1 , 11 ]. As regular repetitions of this intervention are a necessity, dose optimization deserves special consideration and might be beneficial for the patient, the interventional radiologist, and his team alike [ 12 – 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were also 5.7% of patients in the RCT that discontinued treatment because of hepatic toxicity, diagnosed by hyperbilirubinemia (5.7%), increase in ALT (2.9%), and increase in AST (2.9%) [ 16 ]. One retrospective review of 14 patients who underwent PHP found 1 patient who had hepatic failure that resulted in death [ 24 ].…”
Section: Discussionmentioning
confidence: 99%